UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN PISANG EMAS (Musa acuminata Colla.) TERHADAP BAKTERI Staphylococcus aureus - Suharyanisa; Binsar Sitorus; Yenni Gustiani tarigan; Hestina; Suedy Jordan Nainggolan (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
Banana gold (Musa acuminata Colla.) is a type of banana that contains a lot of sugar so that it has a sweeter taste when compared to other types of bananas. So a study was conducted on the test of antibacterial activity of Ethanol extract golden banana leaves (Musa acuminata Colla.) against Staphylococcus aureus bacteria. This study aims to determine the antibacterial activity of ethanol extract of golden banana leaves and find out at what concentrations have the most influence on the inhibitory power of staphylococcus aureus bacteria growth. This study was conducted by extracting Banana Leaves using 96% ethanol by the maceration method, then the extract obtained was made with several concentrations, namely 20, 40, and 80mg/mL. then antibacterial activity testing is carried out by the method of diffusion agar. In ethanol extract against Staphylococcus aureus bacteria with a concentration of 80mg/mL (14.62 ± 0.99) at a concentration of 40mg/mL (14.23 ± 0.70) and at a concentration of 20mg/mL (12.68 ± 0.42). Ethanol extract concentration of 80 mg/mL has a good ability to inhibit the growth of staphylococcus aureus bacteria with an inhibitory zone (14.62 ± 0.99) which is categorized as strong.